Plan de negocio para la creación de roca tecnologies s.a. microempresa que comercializara servicios de auditoría de sistemas y la implementación de un sistema detector de intrusos - Rojas, Soni (2009)
The project includes the presentation of a business plan to market a product and various services in the area of Systems Auditing. We present a prototype design and construction has the function to control the proper use and proper operation of voice and data network of a microenterprise. The system enables timely detection of failure in communication equipment, key network equipment such as servers and services on a team defined. The business plan concludes that it is feasible to our enterprise.